Agile Leadership in Islamic Boarding School: An Exploratory Study of Team Iteration and Collaboration Practices in Times of Disruption: Case Study at Al-Amien Prenduan Islamic Boarding School, Sumenep, Madura - Ahmad Sukandar; Musleh Wahid; Indra Azwar Mawardi; Didik Himmawan (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
This exploratory qualitative study investigates agile leadership practices in Islamic boarding school leadership, focusing on iteration and team collaboration in an era of disruption. The case study was conducted at Al-Amien Prenduan Madura Islamic Boarding School, selected for its long history and adaptive capacity. Data were collected over six months (January–June 2023), a post-COVID-19 transition phase during which Islamic boarding schools were intensifying digital adaptation and organizational restructuring. Collection methods included triangulation through in-depth interviews, participatory observation, and documentation studies involving kiai, senior ustadz, administrators, and senior santri. Data analysis followed reduction, presentation, and conclusion-drawing procedures, with validity assessed through credibility, transferability, dependability, and confirmability. The results show that this pesantren applies agile leadership through a collective system, with the Majlis Kiai (Council of Clerics) serving as a participatory strategic decision-making body. Iterative practices are reflected in continuous planning and evaluation cycles, while team collaboration involves a multi-level decision-making structure. The pesantren demonstrates flexibility in integrating digital technology while preserving its traditional identity through gradual adaptation, supported by an adaptive organizational culture, integrated management, and dialogical communication distinguishing it from traditional salaf pesantren. Theoretically, this study integrates agile leadership concepts into traditional pesantren leadership; practically, it offers an adaptive leadership model for Islamic educational institutions facing disruption. The findings affirm that agile leadership emphasizing iteration and team collaboration can be implemented in Islamic boarding schools without eroding spiritual and traditional values. By balancing Islamic identity with digital adaptation through distributed leadership, this approach enhances learning effectiveness, organizational capacity, and responsiveness to external change.